2015
DOI: 10.1016/j.expneurol.2014.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen preconditioning attenuates hemorrhagic transformation through increasing PPARγ in hyperglycemic MCAO rats

Abstract: Hyperbaric oxygen preconditioning (HBO-PC) has been demonstrated to attenuate hemorrhagic transformation (HT) after middle cerebral artery occlusion (MCAO) in hyperglycemic rats. However, the mechanisms remain to be illustrated. Recently, HBO-PC has been shown to activate peroxisome proliferator-activated receptor-gamma (PPARγ) by increasing 15d-PGJ2 in primary cultured neurons. We hypothesize that HBO-PC reduces HT by suppressing inflammation through increasing 15d-PGJ2 and activating PPARγ in hyperglycemic M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Inflammation may play a critical role in the pathophysiology of hyperglycemia-enhanced hemorrhagic transformation. Recently, our studies found that HBO preconditioning preserved the integrity of blood-brain barrier by suppressing inflammation through the activation of the peroxisome proliferator-activated receptor-γ pathway (23)(24)(25)(26). In this study, we focus on the NLRP3 inflammasome, which have a reported detrimental effect in the ischemic stroke and intracerebral hemorrhage models (10,11,27,28).…”
Section: Discussionmentioning
confidence: 96%
“…Inflammation may play a critical role in the pathophysiology of hyperglycemia-enhanced hemorrhagic transformation. Recently, our studies found that HBO preconditioning preserved the integrity of blood-brain barrier by suppressing inflammation through the activation of the peroxisome proliferator-activated receptor-γ pathway (23)(24)(25)(26). In this study, we focus on the NLRP3 inflammasome, which have a reported detrimental effect in the ischemic stroke and intracerebral hemorrhage models (10,11,27,28).…”
Section: Discussionmentioning
confidence: 96%
“…We prolonged the MCAO time to 5 h to create severe ischemia. To further compromise BBB functions and integrity, we created acute hyperglycemia in our animal model to increase the severity of HT 19. Indeed, most of the HTs in this animal model were parenchymal hematomas, the suppression of which led to an improved neurological score.…”
Section: Discussionmentioning
confidence: 99%
“…At 19 h after reperfusion (24 h after the onset of ischemia) the rats were sacrificed and the brains were harvested for measurements. To increase the extent of cerebral hemorrhage after ischemia/reperfusion, 50% dextrose was injected intraperitoneally at 6 mL/kg before MCAO and at 1.5 ml/kg afterwards to induce acute hyperglycemia in all rats (see online supplementary figure S1) 19…”
Section: Methodsmentioning
confidence: 99%
“…Seventy-five rats were from the initial stage of the study and 31 additional rats were randomly assigned to these three groups to increase the number in each group to reduce the variance of the following measurements. The infarct volume, neurological deficit score, and HT of these rats were assessed blindly according to the Stroke Therapy Academic Industry Roundtable (STAIR) criteria 8 15. Four survival rats were added to three groups for 2,3,5-triphenyltetrazolium chloride (TTC) staining to improve the quantification of infarct volume and HT.…”
Section: Methodsmentioning
confidence: 99%